Ireland : Ninth Review Under the Extended Arrangement. (IMF Staff Country Reports; Country Report, 2013)
A positive financial market and real sector developments support Ireland's capacity to exit the EU-IMF supported program at year's end. But the underlying fiscal and financial situation is still difficult, and continued strong policy execution remains paramount. Improvement in dealing with nonperforming loans and preventing a rise in structural unemployment is critical to strengthen prospects for recovery. Ireland's strong track record of budget execution must be maintained, and building on the recent strengthening of the medium-term budget framework will support a durable exit.